Modelling of seismically induced liquefaction under high confining stress. Issue 3 (September 2002) - Gonzalez, Lenart; Abdoun, Tarek; Sharp, Michael K.
Abstract : Evaluation of seismically-induced liquefaction under high confining stress, such as might relate to the foundation soil under large earth dams, is based on the extrapolation of observed behavior and correlations at shallow depths. In practice, the behavior of saturated sand and other cohesionless soils under these conditions is not well understood. Experiments were conducted, at the 100 g-ton RPI centrifuge facility, to investigate confining stress effects on liquefaction potential, under the boundary and loading conditions of a deep horizontal saturated sand deposit. Three level ground models, with either a homogeneous profile or a dense layer over a loose layer, were tested in a laminar box. In two of the models, a steel plate surcharge was placed on the soil to increase confinement. Recorded accelerations and pore pressures, vertical surface settlement, and shear strains and stresses derived from the accelerations using System Identification, were analyzed to study the effect of high confining stress on the development of soil liquefaction.